Academic Achievement Reflected The Quality of Life and Neurocognitive Status in Malaysian Primary School Children - Vionalita, Gisely; Zalina, I; Aasim, Wa; Ali, Sm (Indonesian Journal of Early Childhood Education Studies, 2018)
Academic achievement is not the only indicator of achievement in school. The neurocognitive profile, as measured by the quality of life (QoL) and neurocognitive status are important markers that make academic achievement more relevant with regard to optimum brain utilization. The main objective of this study was to determine the relationship between quality of life, neurocognitive status and academic achievement in a sample of children in a Malaysian primary school. QoL was measured using three versions of the TNO-AZL quality of life (TACQOL) questionnaire from the children’s (CV), parents’ (PV) and teachers’ (TV) perspectives. Neurocognitive status was assessed in two domains, executive function and visual memory using Cambridge Neuropsychology Tests Automated Battery (CANTAB®). A convenience sampling was undertaken for all 95 Standard One Zainab 2 Primary School children (7 Years Old), 95 parents and 4 teachers. Regarding executive function, 42.1% of children experienced difficulties in extra dimensional shift which measures attention flexibility in accepting a new rule. However, they performed well in the intra extra dimensional shift, indicating that most children responded positively to experiential learning. For visual memory, 49.5% of children experienced some difficulties in terms of their short term visual memory. The relationship between QoL, neurocognitive status and academic achievement of the children showed that only ‘cognitive complaint’ and ‘negative mood’ had a significant linear positive relationship with academic achievement. No other significant relationship was noted between neurocognitive status and academic achievement. Thus, this study has shown that academic achievement does not necessarily reflect the neurocognitive status of children implying that some neurocognitive problems remain undetected. A more meaningful assessment of academic achievement, in primary schools should include an assessment of both QoL and neurocognitive profile. Keywords : CANTAB, primary school children, cognitive status, academic achievement.